Impact of Greenwashing and Perceived Value on Purchase Intention in the Bottled Drinking Water Industry: Mediating Role of Trust - Rifai Apriture Afianto; Jati Waskito (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study investigates the effects of greenwashing and green perceived value on green purchase intention, with green trust serving as a mediating variable. It aims to provide deeper insights into the factors shaping consumer decisions when choosing bottled drinking water products.Method: A quantitative research approach was employed, using questionnaires to collect primary data from 200 respondents in the Solo Raya region who had purchased or consumed Le Minerale products. Respondents were selected through purposive sampling to ensure alignment with the study's objectives. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SMARTPLS software.Result: The findings reveal that both greenwashing and green perceived value significantly influence green trust, which, in turn, mediates their impact on green purchase intention. This highlights the pivotal role of transparency in sustainability claims and emphasizes the need for companies to communicate authentic environmental benefits. By fostering trust, businesses can promote long-term sustainable consumption behaviors and strengthen consumer confidence in green products.Practical Implications for Economic Growth and Development: This study underscores the importance of transparency and consistent communication in building consumer trust in environmental commitments. Such efforts not only expand the market for eco-friendly products but also contribute to the development of a more sustainable economy. Moreover, minimizing greenwashing practices can drive innovation and encourage sustainability-focused production processes, supporting both economic growth and environmental responsibility.